Alien Freshwater Fish Cultured in Malaysia: Economic Development or Native Fish Species Extinctions - Khairul Adha, A. Rahim (2017)
Human activities to increase economic productivity and food supplies have contributed to the introduction of alien fish into freshwater ecosystems. The introduction of alien fishes for aquaculture, recreational fisheries, stocking enhancement, biological control and aquarium fish industry has also led to the establishment of alien species in local aquatic habitats. More than 24 species of alien fishes, mainly for culture have been introduced into Malaysian fresh waters for the past 40 years. It is likely that alien species in Malaysia have positive impacts on various economies in the country. Despite some arguably positive effects on biodiversity at the local scale, an overwhelming amount of evidence indicates the profoundly negative effects of alien species introduction on genetic diversity as a whole. Presently, there are neither documented information nor specific research programs in Malaysia about the roles and contributions of alien fish on aquaculture development as well as the impacts on other native fish fauna. Therefore, the documentation of the influence and the effects of alien fish species on aquaculture development in Malaysia is vital. If alien species abundance increases in the future, it will be easier to identify changes, particularly on native fish fauna and other natural resource related to the increased abundance of alien fish or other causes.